Preparing loan proposals - Wisdom, John C. (Small business workbooks, 1997)
This book shows small business owners and their financial advisors how to prepare well-documented loan proposals. It helps preparers improve their chances of getting a loan approved by helping them understand what lenders look for when evaluating a loan proposal.